TINJAUAN HUKUM TATA NEGARA ISLAM TERHADAP (TRANSPARANSI ANGGARAN PENDAPATAN BELANJA DAERAH) (STUDI KASUS DI KOTA MAKASSAR) - Iqbal, Andi Muhammad; Sastrawati, Nila (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2020)
This research is about how the Review of Islamic State Governance Law on Transparency of Regional Expenditure Budget (case study in Makassar City). The main problems are: 1) What is the Format of Budget Transparency in Makassar City, 2) What is the View of Islamic State Administration Law on Transparency of Regional Expenditure Budget in Makassar City? This type of research is conducted qualitatively in the field using descriptive research methods, data collection techniques with observation methods, interviews, and documentation. The results of the study show that in the review of Islamic constitutional law on the transparency of the regional budget (case study in the city of Makassar), including openness and transparency of government administration in Makassar City is still relatively minimal. The concept of transparency in Islamic teachings has relevance to the prophetic nature of the prophet Muhammad. This is reinforced by what Muhammad Syafi'i Antonio said that the prophetic values of business and management inherent in Rasulullah Saw include: Siddiq, right, the basic value is integrity. The implications of this research are: 1) The government opens information services to increase transparency to the public, 2) It is hoped that the government can further increase the socialization and publication of transparency to the public.